2018
DOI: 10.1016/j.actbio.2018.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Puncturing of lyophilized tissue engineered vascular matrices enhances the efficiency of their recellularization

Abstract: The concept of living tissue engineered, self-repairing, autologous cardiovascular replacements, was proposed alternatively to existing synthetic/xenogeneic prostheses. Recent studies in animal models demonstrate faster in vivo recellularization after grafts pre-seeding with cells prior implantation. Pre-seeded cells hold either, the ability to differentiate directionally or attract host cells, crucial for graft integration and remodeling. It is unclear, however, how efficient the pre-loading is and how well c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
2
0
2
Order By: Relevance
“…Researchers have been attempting to improve its performance. Agnieszka et al [ 15 ] has compared different reseeding methods to define the most efficient technique enhancing recellularization of tissue engineered vascular vessels prior implantation. They found that puncturing of lyophilized tissue engineered vascular matrices could enhance the efficiency of their recellularization.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have been attempting to improve its performance. Agnieszka et al [ 15 ] has compared different reseeding methods to define the most efficient technique enhancing recellularization of tissue engineered vascular vessels prior implantation. They found that puncturing of lyophilized tissue engineered vascular matrices could enhance the efficiency of their recellularization.…”
Section: Introductionmentioning
confidence: 99%
“…В недавнем исследовании Ksiazek с коллегами предложили собственный подход к созданию ТИЗ [40]. Нетканный пористый материал из PGA покрывали быстро деградируемым P-4-HB, а затем заселяли фетальными ММСК овцы.…”
Section: аналитический обзорunclassified
“…Также авторы установили, что наилучшим способом заселения данного матрикса мононуклеарными клетками является предварительная лиофилизация материала с нанесением клеточной суспензии комбинированным методом капельного и инъекционного введения. Данный подход позволил доставить клетки в центр матрикса, несмотря на плотное расположение коллагеновых волокон в децеллюляризированном материале [40].…”
Section: аналитический обзорunclassified
“…Recently, Książek et al proposed a “puncturing-dripping” method for re-seeding tissue-engineered vascular matrices. The results demonstrated that the highest cell-loading efficiency was observed after lyophilization followed by the puncturing-dripping technique [ 60 ]. A dynamic culture system typically involves a pulsatile perfusion bioreactor to simulate blood flow/flow rate in vivo [ 61 ].…”
Section: Introductionmentioning
confidence: 99%